AFIKS INFLEKSI PADA LIRIK LAGU KARYA BRUNO MARS DALAM ALBUM DOO-WOPS & HOOLIGANS - DONGALEMBA, STEPHANIE GABRILA; KODONG, FENTJE; LOTULUNG, DONALD RINGGO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ  This research entitled â€œAfiks Infleksi pada Lirik Lagu Karya Bruno Mars dalam Album Doo-Wops & Hooligansâ€. It is written to identify, classify and analyze the forms and the functions of inflectional affixes in the lyrics of Bruno Marsâ€™ album Doo-Wops & Hooligans. The method that used in this research is the descriptive method, and the data of inflectional affixes were taken from album Doo-Wops & Hooligans by means of identifying and classifying them according to their form and function. The data have been analyzed using the theory of Oâ€™ Grady and Dobrovolsky. The forms and functions of the inflectional affixes that have been found in the lyrics of Bruno Marsâ€™ album Doo-Wops & Hooligans are {-s/-es} which function as plural, {â€™s} which functions as possessive, {-s/-es} which function as 3rd person singular, {-ing} which functions as progressive, {-ed} which functions as past tense, {-ed/-en} which function as past participle, and {-er} which functions as comparative. There is no allomorph /-iz/ found in plural {-es} and 3rd person singular {-es}, there is also no allomorph /-t/ and /-id/ in past participle {-ed} that found in the lyrics of Bruno Marsâ€™ album Doo-Wops & Hooligans. Superlative {-est} is not found on this album. Progressive {-ing}, past participle {-en}, and comparative {-er} are not divided into several allomorph because theyâ€™re only have one allomorph, namely /-iÅ‹/, /-É™n/, and /É™r/. Possessive {â€™s} does not produce allomorph /-z/ when nouns end with allomorph /s/. Theoretically, this research is intended to add to the research of linguistic research, especially in the field of morphology about affixation. Practically, it is expected to be a comparative material for other researchers who will analyze the same thing in linguistic field, and can provide information to increase readerâ€™s knowledge on linguistic especially inflectional affixes.Â _____________________Keywords: Inflectional Affixes, Morphology, Doo-Wops & Hooligans Album